2013
DOI: 10.1080/09593330.2012.710410
|View full text |Cite
|
Sign up to set email alerts
|

Optical monitoring of activated sludge flocs in bulking and non-bulking conditions

Abstract: This study introduces a novel optical monitoring method to image and characterize activated sludge flocs and to study the dependency of sludge settling properties on the floc structure. The novel method can easily analyse thousands of particles in a short timeframe using the developed image analysis program. The main advantage of this method is its applicability for in situ use because the only required pre-treatment is sample dilution. This study tested real process samples from activated sludge plants treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…To replace a laborious, slow and subjective method to study wastewater samples manually using a microscope, a small-scale automatic optical monitoring device was designed [10] and applied to analyze the wastewater samples taken from the aeration tank of the industrial ASP. Wastewater samples were diluted with deionized water at a ratio of 1:200 and pumped through a cuvette which was imaged with a high resolution charge-coupled device (CCD) camera.…”
Section: Optical Monitoring and Image Analysismentioning
confidence: 99%
“…To replace a laborious, slow and subjective method to study wastewater samples manually using a microscope, a small-scale automatic optical monitoring device was designed [10] and applied to analyze the wastewater samples taken from the aeration tank of the industrial ASP. Wastewater samples were diluted with deionized water at a ratio of 1:200 and pumped through a cuvette which was imaged with a high resolution charge-coupled device (CCD) camera.…”
Section: Optical Monitoring and Image Analysismentioning
confidence: 99%
“…What is more, activated sludge was usually taken from one sampling point located in the aeration zone of an activated sludge system. [5,11,14] It means that the variability of sludge floc morphology along the activated sludge chamber containing zones with different oxido-reductive conditions has not been studied yet.…”
Section: Introductionmentioning
confidence: 98%
“…It was demonstrated that image analysis was a useful tool to characterize activated sludge biomass in terms of floc size and its relation to the settling properties and concentration of biomass. [8][9][10][11][12] Mesquita et al [5] proved that the image analysis methodology was adequate for a continuous examination of the morphological changes of aggregates and subsequent prediction of the sludge volume index (SVI). At the same time, image analysis combined with chemometric techniques can be applied to identify activated sludge abnormalities, namely pinpoint floc formation and filamentous and zoogleal bulking.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 shows the results of image analysis. All samples show the same roundness (Koivuranta et al, 2013) Table 4 Results of image analysis of SEM images, helium pycnometry and N 2 adsorption of tailing samples.…”
Section: Resultsmentioning
confidence: 99%